High-toughness hydrogen-corrosion-resistant stainless steel pipe and preparation method thereof

By adjusting the nickel and chromium content and adding elements such as V, Mo, Co, Yi to form a composite metal phase, combined with quenching and tempering treatment, the problem of stainless steel pipes being prone to hydrogen corrosion and hydrogen embrittlement at high temperatures is solved, and high toughness and hydrogen corrosion resistance are improved, while maintaining the yield strength.

CN119506719AInactive Publication Date: 2025-02-25ZHEJIANG FONYE GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510092808.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing stainless steel pipes are prone to hydrogen corrosion and hydrogen embrittlement at high temperatures, resulting in a decline in material performance, limiting their application scenarios, and it is difficult to maintain hardness and yield strength when improving toughness.

Method used

By adjusting the nickel content and increasing the chromium content, and adding specific contents of V, Mo, Co, Yi, to form a composite metallographic phase, combined with heat treatment of quenching and tempering, the metallographic structure is optimized, and toughness and hydrogen corrosion resistance are improved.

Benefits of technology

It achieves good toughness and hydrogen corrosion resistance of stainless steel pipes at high temperatures, while maintaining yield strength, extending the incubation period of pearlite transformation, and stably stably quenching process supercooled austenite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-toughness hydrogen-corrosion-resistant stainless steel pipe and a preparation method thereof.The high-toughness hydrogen-corrosion-resistant stainless steel pipe is obtained through pipe blank rolling, quenching and tempering and comprises, by mass, 0.11%-0.15% of C, 0.4%-0.6% of Si, 18.2%-19.6% of Cr, 3.2%-4.6% of Ni, 0.7%-0.9% of V, 1.2%-2.4% of Mo, 1.1%-1.7% of Co, 0.8%-1.1% of Yi, smaller than or equal to 0.01% of S, smaller than or equal to 0.002% of P and the balance Fe and inevitable impurities; the steel plate has excellent comprehensive performance of yield strength and toughness and excellent hydrogen corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to stainless steel materials, and in particular to a high-toughness, hydrogen-corrosion-resistant stainless steel pipe and a preparation method thereof. Background Art

[0002] Stainless steel pipes are widely demanded in industrial applications, especially in the fields of petroleum, chemical industry, aerospace, etc.

[0003] Stainless steel pipes are used in special fields such as hydrogen production and chemical production. The medium and environment contain hydrogen. The surrounding environment is hot and humid, which is prone to hydrogen corrosion and hydrogen embrittlement, resulting in material performance degradation or even failure. This not only affects the service life of stainless steel pipes, but also limits the application scenarios of stainless steel pipes. For example, although stainless steel with a high chromium content has good corrosion resistance, it will become more brittle after long-term high-temperature service, affecting its service life and safety.

[0004] Existing stainless steel pipes use a composition adjustment method. Although it can significantly improve toughness to resist hydrogen corrosion, this often reduces the hardness of the pipe, thereby reducing the yield resistance of the pipe when it is impacted. These problems have seriously restricted the application and development of high-end stainless steel pipes. It is urgent to develop a stainless steel pipe that can maintain good toughness and hydrogen corrosion resistance at high temperatures while ensuring the yield strength of the pipe. Summary of the invention

[0005] In order to improve the toughness and hydrogen corrosion resistance of a stainless steel pipe, a high-toughness hydrogen corrosion-resistant stainless steel pipe and a preparation method thereof are provided.

[0006] The above first invention objective of the present invention is achieved through the following technical solutions: A high-toughness, hydrogen-corrosion-resistant stainless steel pipe comprising the following components by mass fraction: C 0.11~0.15%, Si 0.4~0.6%, Cr 18.2~19.6%, Ni 3.2~4.6%, V 0.7~0.9%, Mo 1.2~2.4%, Co 1.1~1.7%, Yi 0.8~1.1%, S≤0.01%, P≤0.002%, Others are Fe and unavoidable impurities; It is obtained by rolling, quenching and tempering the tube billet.

[0007] By adopting the above technical solution, the nickel content is adjusted and the chromium content is increased to enhance the hydrogen corrosion resistance of the stainless steel pipe at high temperature. At the same time, a specific amount of V, Mo, Co, and Yi are added to the iron grains to form Fe-M A 、Fe-M A -M B (M A 、M B The composite metallographic structure is one of V, Mo, Mn, Co, and Yi. Combined with the heat treatment of quenching and tempering, the composite metallographic structure can enhance the toughness of stainless steel pipes, repair the increased brittleness caused by high chromium content and the increased tempering brittleness caused by secondary hardening caused by chromium during tempering. On the other hand, V, Mo, Mn, Co, and Yi are self-dispersed and self-diffused during tempering, optimizing the dispersion of composite metallographic structure, thereby extending the pearlite transformation incubation period, thereby improving the stability of supercooled austenite, stabilizing the supercooled austenite in the quenching process, and resetting the austenite after tempering, thereby realizing the regulation of the distribution and transformation of metallographic structures such as pearlite, austenite, and martensite, so that the stainless steel pipes have excellent comprehensive properties of yield strength and toughness as well as excellent hydrogen corrosion resistance.

[0008] A high-toughness, hydrogen-corrosion-resistant stainless steel pipe comprising the following components by mass fraction: C 0.11~0.15%, Si 0.4~0.6%, Cr 18.2~19.6%, Ni 3.2~4.6%, V 0.7~0.9%, Mo 1.2~2.4%, Co 1.1~1.7%, Yi 0.8~1.1%, Ta 0.4-0.6%, wherein Ta is added as tantalum carbide; S≤0.02%, P≤0.002%, Others are Fe and unavoidable impurities; It is obtained by rolling, quenching and tempering the tube billet.

[0009] By adopting the above technical solution, the addition of tantalum carbide can promote the fine grain strengthening effect. The fine carbide particles are distributed in the matrix, which can effectively inhibit grain growth and refine austenite, thereby further adjusting the austenite metallographic structure, thereby improving the mechanical properties and stability of the material.

[0010] A method for preparing a high-toughness, hydrogen-corrosion-resistant stainless steel pipe comprises the following steps: smelting, continuous casting, drilling, rolling, quenching and tempering.

[0011] Optional: the quenching temperature is 1120~1130℃, and the cooling temperature is 75~90℃ on the surface.

[0012] By adopting the above technical solution, the mechanical properties and stability of the material obtained after quenching treatment are better, and the stainless steel pipe obtains excellent comprehensive properties of yield strength and toughness as well as excellent hydrogen corrosion resistance.

[0013] Optional: the tempering temperature is 769-780°C, and the tempering temperature time is 1.6 min / mm (tube wall thickness).

[0014] By adopting the Shangfangshan technical solution, the A1 temperature of the stainless steel pipe of the component of this application is 656~682℃, the tempering temperature is controlled at 749~755℃, and the tempering temperature time is controlled at 1.6min / mm (pipe wall thickness), which can effectively transform pearlite and supercooled austenite into austenite and bainite again, effectively adjust the metallographic structure of the stainless steel pipe, and stably improve the comprehensive performance of the yield strength and toughness and corrosion resistance of the stainless steel pipe.

[0015] Optionally, the tempered stainless steel pipe is cooled to room temperature in a protective atmosphere containing nitrogen.

[0016] By adopting the above technical scheme, cooling is carried out under a nitrogen protective atmosphere after tempering. On the one hand, the changes in the precipitation structure and distribution of carbon elements on the surface of the stainless steel pipe due to oxidation are reduced, thereby avoiding the weakening of the surface hardness of the stainless steel pipe caused by this. On the other hand, the surface of the stainless steel pipe is nitrided during the cooling process, and the surface of the stainless steel pipe is micro-alloyed and modified, thereby improving the hydrogen corrosion resistance of the stainless steel pipe surface.

[0017] Optionally, the nitrogen content of the nitrogen-containing protective atmosphere is 82.9-84.6 vol%.

[0018] By adopting the above technical solution, the micro-alloying modification effect of the stainless steel pipe surface is better, and the anti-hydrogen corrosion performance of the obtained stainless steel pipe surface is better.

[0019] A method for preparing a high-toughness, hydrogen-corrosion-resistant stainless steel pipe comprises the following steps: smelting, continuous casting, drilling, rolling, quenching and tempering. The tantalum carbide is added to molten steel during the smelting process. The tantalum carbide is added in the form of a composite solid solution of tantalum carbide and iron-nickel alloy.

[0020] By adopting the above technical solution, tantalum carbide can be dispersed more evenly in molten steel, the grain refining effect of tantalum carbide can be improved, and the toughness and hydrogen corrosion resistance of stainless steel pipes can be enhanced.

[0021] In summary, this application has at least the following beneficial effects: The nickel content is adjusted and the chromium content is increased to enhance the hydrogen corrosion resistance of stainless steel pipes at high temperatures. At the same time, a specific content of V, Mo, Co, and Yi is added to dissolve in the iron grains to form a composite metallographic phase. Combined with the heat treatment of quenching and tempering, on the one hand, the toughness of stainless steel pipes is enhanced, the increased brittleness caused by high chromium content and the increased tempering brittleness caused by secondary hardening caused by chromium during tempering are repaired. On the other hand, V, Mo, Mn, Co, and Yi self-disperse and self-diffuse during tempering, optimize the dispersion of composite metallographic phases, and then extend the pearlite transformation incubation period, thereby improving the stability of supercooled austenite, stabilizing the supercooled austenite in the quenching process, and resetting the austenite after tempering, thereby achieving the regulation of the distribution and transformation of metallographic structures such as pearlite, austenite, and martensite, so that the stainless steel pipe obtains excellent comprehensive performance of yield strength and toughness as well as excellent hydrogen corrosion resistance. DETAILED DESCRIPTION

[0022] raw material The steel ingot and alloy ingot are both commercially available products; the tantalum carbide is nano-scale tantalum carbide with a particle size of 400nm; the composite solid solution of tantalum carbide and iron-nickel alloy is obtained by adding nano-scale tantalum carbide to molten iron-nickel alloy, mixing at 1120°C for 1h and then casting into an ingot. The mass ratio of tantalum carbide to iron-nickel alloy is 3:40.

[0023] Embodiment 1~4 A high-toughness, hydrogen-corrosion-resistant stainless steel pipe comprises the following components by mass fraction: C 0.11-0.15%, Si 0.4-0.6%, Cr 18.2-19.6%, Ni 3.2-4.6%, V 0.7-0.9%, Mo 1.2-2.4%, Co 1.1-1.7%, Yi 0.8-1.1%, S≤0.01%, P≤0.002%, and the rest are Fe and unavoidable impurities.

[0024] The specific preparation method is as follows: According to the composition requirements, steel ingots and alloy ingots will be prepared, smelted and refined, and the molten steel composition and carbon endpoint will be controlled to C≤0.15%, S≤0.01% and P≤0.002% in impurities to obtain molten steel; The molten steel is continuously cast at a continuous casting speed of 1.7 m / min to obtain a round billet; The round billet is pierced, the round billet temperature is 1280°C, and the piercing temperature is 1220°C to obtain a tube billet; The tube billet is rolled, the final rolling temperature is controlled to be 925°C, and the final rolling is tension-reduced at a temperature of 895°C to obtain a rough billet, wherein the wall thickness of the rough billet in this application is 12±0.2mm; The rough blank is quenched at a quenching temperature of 1125°C and a holding time of 50 minutes until the surface temperature of the rough blank is 80°C. The rough blank is then tempered at a tempering temperature of 776°C and a tempering holding time of 1.6 minutes / mm (wall thickness of the pipe), that is, a tempering holding time of 19.2 minutes. After the treatment, a hot pipe is obtained. The hot pipe is heat-sized and heat-straightened at a temperature of 528°C. After the treatments of heat sizing and heat straightening, the hot pipe is placed in a protective atmosphere of 83.9wt% nitrogen and slowly cooled to room temperature to obtain a high-toughness, hydrogen-corrosion-resistant stainless steel pipe.

[0025] The components of the stainless steel pipes of Examples 1 to 4 were tested, and the results are shown in Table 1 below.

[0026] Table 1. Composition of stainless steel pipes in Examples 1 to 4

[0027] The remaining components are Fe and inevitable impurities.

[0028] Embodiments 5 to 8 A high-toughness, hydrogen-corrosion-resistant stainless steel pipe comprises the following components by mass fraction: C 0.11-0.15%, Si 0.4-0.6%, Cr 18.2-19.6%, Ni 3.2-4.6%, V 0.7-0.9%, Mo 1.2-2.4%, Co 1.1-1.7%, Yi 0.8-1.1%, Ta 0.4-0.6%, S≤0.02%, P≤0.002%, and the rest are Fe and unavoidable impurities, wherein Ta is added as tantalum carbide.

[0029] The specific preparation method is as follows: According to the composition requirements, solid solutions, steel ingots and alloy ingots of niobium carbide and iron-nickel alloy are prepared, and molten steel is obtained after smelting and refining, and the composition of molten steel is controlled, the carbon end point is controlled to C≤0.15%, and S≤0.01% and P≤0.002% in impurities; The molten steel is continuously cast at a continuous casting speed of 1.7 m / min to obtain a round billet; The round billet is pierced, the round billet temperature is 1280°C, and the piercing temperature is 1220°C to obtain a tube billet; The tube billet is rolled, the final rolling temperature is controlled to be 925°C, and the final rolling is tension-reduced at a temperature of 895°C to obtain a rough billet. In this application, the wall thickness of the rough billet is 12±0.2mm, and the outer diameter is 100±2mm; The rough blank is quenched at a quenching temperature of 1125°C and a holding time of 50 minutes until the surface temperature of the rough blank is 86°C. The rough blank is then tempered at a tempering temperature of 776°C and a tempering holding time of 1.6 minutes / mm (wall thickness of the pipe), that is, a tempering holding time of 19.2 minutes. After the treatment, a hot pipe is obtained; The hot pipe is heat-sized and heat-straightened at a temperature of 528°C. After the treatments of heat sizing and heat straightening, the hot pipe is placed in a protective atmosphere of 83.9 vol% nitrogen and slowly cooled to room temperature to obtain a stainless steel pipe with high toughness and resistance to hydrogen corrosion.

[0030] Example 9 A high-toughness, hydrogen-corrosion-resistant stainless steel pipe comprises the following components by mass fraction: C 0.11-0.15%, Si 0.4-0.6%, Cr 18.2-19.6%, Ni 3.2-4.6%, V 0.7-0.9%, Mo 1.2-2.4%, Co 1.1-1.7%, Yi 0.8-1.1%, Ta 0.4-0.6%, S≤0.02%, P≤0.002%, and the rest are Fe and unavoidable impurities, wherein Ta is added as tantalum carbide.

[0031] The specific preparation method is as follows: According to the composition requirements, niobium carbide, steel ingots and alloy ingots are prepared, smelted and refined, and the molten steel composition is controlled, the carbon end point is controlled to C≤0.15%, S≤0.01% and P≤0.002% in impurities, to obtain molten steel; The molten steel is continuously cast at a continuous casting speed of 1.7 m / min to obtain a round billet; The round billet is pierced, the round billet temperature is 1280°C, and the piercing temperature is 1220°C to obtain a tube billet; The tube billet is rolled, the final rolling temperature is controlled to be 925°C, and the final rolling is tension-reduced at a temperature of 895°C to obtain a rough billet, wherein the wall thickness of the rough billet in this application is 12±0.2mm; The rough blank is quenched at a quenching temperature of 1125°C and a holding time of 50 minutes until the surface temperature of the rough blank is 86°C. The rough blank is then tempered at a tempering temperature of 776°C and a tempering holding time of 1.6 minutes / mm (wall thickness of the pipe), that is, a tempering holding time of 19.2 minutes. After the treatment, a hot pipe is obtained; The hot pipe is heat-sized and heat-straightened at a temperature of 528°C. After the treatments of heat sizing and heat straightening, the hot pipe is placed in a protective atmosphere of 83.9 vol% nitrogen and slowly cooled to room temperature to obtain a stainless steel pipe with low toughness and hydrogen corrosion resistance.

[0032] The components of the stainless steel pipes of Examples 5 to 9 were tested, and the results are shown in Table 2 below.

[0033] Table 2. Composition of stainless steel pipes in Examples 5 to 9

[0034] The remaining components are Fe and inevitable impurities.

[0035] Embodiments 10 to 17 A high-toughness, hydrogen-corrosion-resistant stainless steel pipe is made from the same batch of rough blanks as Example 7, except that the parameters of the quenching and tempering treatments of the rough blanks are different, as shown in Table 3 below.

[0036] Table 3. Quenching and tempering parameters of Examples 10 to 17

[0037] Embodiments 18 to 22 A high-toughness, hydrogen-corrosion-resistant stainless steel pipe is from the same batch of hot pipes as Example 7, except that the ambient atmosphere for cooling the hot pipes is different, as shown in Table 4 below.

[0038] Table 4. Ambient atmosphere for cooling the hot pipes of Examples 18 to 22

[0039] Comparative Examples 1 to 4 A stainless steel pipe comprises the following components in mass fraction: C 0.11-0.15%, Si 0.4-0.6%, Cr18.2-19.6%, Ni 3.2-4.6%, S≤0.01%, P≤0.002%, and the rest are Fe and unavoidable impurities.

[0040] The specific preparation method is as follows: According to the composition requirements, steel ingots and alloy ingots will be prepared, smelted and refined, and the molten steel composition and carbon endpoint will be controlled to C≤0.15%, S≤0.01% and P≤0.002% in impurities to obtain molten steel; The molten steel is continuously cast at a continuous casting speed of 1.7 m / min to obtain a round billet; The round billet is pierced, the round billet temperature is 1280°C, and the piercing temperature is 1220°C to obtain a tube billet; The tube billet is rolled, the final rolling temperature is controlled to be 925°C, and the final rolling is tension-reduced at a temperature of 895°C to obtain a rough billet, wherein the wall thickness of the rough billet in this application is 12±0.2mm; The rough blank is quenched at a quenching temperature of 1125°C and a holding time of 50 minutes until the surface temperature of the rough blank is 86°C. The rough blank is then tempered at a tempering temperature of 776°C and a tempering holding time of 1.6 minutes / mm (wall thickness of the pipe), that is, a tempering holding time of 19.2 minutes. After the treatment, a hot pipe is obtained; The hot pipe is heat-sized and heat-straightened at a temperature of 528°C. After the treatments of heat sizing and heat straightening, the hot pipe is placed in a protective atmosphere of 83.9 vol% nitrogen and slowly cooled to room temperature to obtain a stainless steel pipe.

[0041] The components of the stainless steel pipes of Comparative Examples 1 to 4 were tested, and the results are shown in Table 5 below.

[0042] Table 5. Stainless steel pipe composition test table of comparative examples 1 to 4

[0043] The remaining components are Fe and inevitable impurities.

[0044] The stainless steel pipes obtained in Examples 1 to 22 and Comparative Examples 1 to 4 were tested, including hardness, yield strength, toughness, and hydrogen corrosion resistance.

[0045] Hardness test: HV-1000S Vickers hardness tester is used for testing, and the results are expressed in Vickers hardness.

[0046] Yield Strength: Tested in accordance with GB / T 229-2020 and the results are expressed as yield strength.

[0047] Toughness test: Toughness test is expressed in terms of impact absorption capacity; the impact absorption capacity is tested by cutting 5 specimens from the stainless steel pipe according to GB / T 229-2020, and the result is expressed as the average value.

[0048] Hydrogen corrosion resistance: In terms of hydrogen embrittlement sensitivity, according to GB / T 34542.3-2018, 10 samples were taken from the stainless steel pipe and processed into discs with a diameter of 58 mm and a thickness of 0.75 mm. Comparative experiments were conducted with helium and hydrogen respectively. Both helium and hydrogen pressurized the disc samples at a constant 0.1 MPa / min until the disc samples burst. The burst pressure P1 in the helium environment and the burst pressure P2 in the hydrogen environment were recorded, and then the hydrogen embrittlement sensitivity coefficient α=P1 / P2 was calculated. The larger α is, the worse the hydrogen corrosion resistance is.

[0049] Table 6. Test results of Examples 1 to 22 and Comparative Examples 1 to 4

[0050] In conjunction with Table 1, by comparing Example 1 with Comparative Example 1, Example 2 with Comparative Example 2, Example 3 with Comparative Example 3, and Example 4 with Comparative Example 4 one by one, it can be seen that: The hardness and yield strength of Example 1 are similar to those of Comparative Example 1, but the impact absorption capacity of Example 1 is significantly greater than that of Comparative Example 1, and the hydrogen embrittlement sensitivity of Example 1 is significantly less than that of Comparative Example 1. Therefore, the hardness and yield strength of Example 1 are similar to those of Comparative Example 1, but the toughness and hydrogen corrosion resistance of Example 1 are significantly better than those of Comparative Example 1. The hardness and yield strength of Example 2 are similar to those of Comparative Example 2, but the impact absorption capacity of Example 2 is significantly greater than that of Comparative Example 2, and the hydrogen embrittlement sensitivity of Example 2 is significantly less than that of Comparative Example 2. Therefore, the hardness and yield strength of Example 2 are similar to those of Comparative Example 2, but the toughness and hydrogen corrosion resistance of Example 2 are significantly better than those of Comparative Example 2. The hardness and yield strength of Example 3 are similar to those of Comparative Example 3, but the impact absorption capacity of Example 1 is significantly greater than that of Comparative Example 3, and the hydrogen embrittlement sensitivity of Example 3 is significantly less than that of Comparative Example 3. Therefore, the hardness and yield strength of Example 3 are similar to those of Comparative Example 3, but the toughness and hydrogen corrosion resistance of Example 3 are significantly better than those of Comparative Example 3. The hardness and yield strength of Example 4 are similar to those of Comparative Example 4, but the impact absorption capacity of Example 4 is significantly greater than that of Comparative Example 4, and the hydrogen embrittlement sensitivity of Example 4 is significantly lower than that of Comparative Example 4. Therefore, the hardness and yield strength of Example 4 are similar to those of Comparative Example 4, but the toughness and hydrogen corrosion resistance of Example 4 are significantly better than those of Comparative Example 4.

[0051] Compared with the corresponding comparative examples in comparative examples 1 to 4, specific contents of V, Mo, Co, and Yi are added to solid-dissolve in the iron grains to form Fe-M A 、Fe-M A -M A (M A 、M B The composite metallographic structure is one of V, Mo, Mn, Co, and Yi. Combined with the heat treatment of quenching and tempering, the composite metallographic structure can enhance the toughness of stainless steel pipes, repair the increased brittleness caused by high chromium content and the increased tempering brittleness caused by secondary hardening caused by chromium during tempering. On the other hand, V, Mo, Mn, Co, and Yi are self-dispersed and self-diffused during tempering, optimizing the dispersion of composite metallographic structure, thereby extending the pearlite transformation incubation period, thereby improving the stability of supercooled austenite, stabilizing the supercooled austenite in the quenching process, and resetting the austenite after tempering, thereby realizing the regulation of the distribution and transformation of metallographic structures such as pearlite, austenite, and martensite, so that the stainless steel pipes have excellent comprehensive performances of hardness, yield strength, and toughness, as well as excellent hydrogen corrosion resistance.

[0052] In addition, the present application is further improved on the basis of Examples 1 to 4 by adding tantalum carbide to the stainless steel pipe. Tantalum carbide can promote the fine grain strengthening effect. The fine carbide particles are distributed in the matrix, which can effectively inhibit grain growth and refine the austenite, thereby further adjusting the austenite metallographic structure, thereby improving the mechanical properties and stability of the material.

[0053] By comparing Example 1 with Example 5, Example 2 with Example 6, Example 3 with Example 7, Example 4 with Example 8 one by one, it can be seen that: The hardness and yield strength of Example 5 are similar to those of Example 1, but the impact absorption capacity of Example 5 is greater than that of Example 1, and the hydrogen embrittlement sensitivity of Example 5 is less than that of Example 1. Therefore, the hardness and yield strength of Example 5 are similar to those of Example 1, but the toughness and hydrogen corrosion resistance of Example 5 are significantly better than those of Example 1. The hardness and yield strength of Example 6 are similar to those of Example 2, but the impact absorption capacity of Example 6 is greater than that of Example 2, and the hydrogen embrittlement sensitivity of Example 6 is less than that of Example 2. Therefore, the hardness and yield strength of Example 6 are similar to those of Example 2, but the toughness and hydrogen corrosion resistance of Example 6 are better than those of Example 2. The hardness and yield strength of Example 7 are similar to those of Example 3, but the impact absorption capacity of Example 7 is greater than that of Example 3, and the hydrogen embrittlement sensitivity of Example 7 is less than that of Example 3. Therefore, the hardness and yield strength of Example 7 are similar to those of Example 3, but the toughness and hydrogen corrosion resistance of Example 7 are better than those of Example 3. The hardness and yield strength of Example 8 are similar to those of Example 4, but the impact absorption capacity of Example 8 is greater than that of Example 4, and the hydrogen embrittlement sensitivity of Example 8 is less than that of Example 4. Therefore, the hardness and yield strength of Example 8 are similar to those of Example 4, but the toughness and hydrogen corrosion resistance of Example 8 are better than those of Comparative Example 4.

[0054] Furthermore, in combination with the detection performance and the carbon content changes in the stainless steel pipe in Examples 1 to 4 and Examples 5 to 8, it can be seen that: Compared with Example 2, Example 3 achieves better performance results through the adaptation and coordination of other internal components when the carbon content is increased; Compared with Example 6, Example 7 achieves better performance results through the adaptation and coordination of other internal components when the carbon content is increased; Therefore, Examples 3 and 7 are the better solutions discovered during the research process of this application.

[0055] By comparing Example 7 and Example 9, it can be seen that the difference between the two is that the way in which tantalum carbide is added to molten steel during the process of obtaining the round billet is different. In the test results, the impact absorption capacity of Example 7 is greater than that of Example 9, the hydrogen embrittlement sensitivity of Example 7 is less than that of Example 9, and the toughness and hydrogen corrosion resistance of Example 7 are better than those of Example 9. Therefore, tantalum carbide is added in the form of a composite solid solution of tantalum carbide and iron-nickel alloy, which better improves the toughness and hydrogen corrosion resistance of the stainless steel pipe.

[0056] By comparing Example 7 with Examples 10 to 13, it can be seen that the difference lies in the different quenching process parameters. In the test results, the hardness and yield strength are from high to low in the order of Example 7, Example 13, Example 12, Example 11, and Example 10, the toughness is from best to worst in the order of Example 7, Example 12, Example 11, Example 13, and Example 10, and the hydrogen corrosion resistance is from best to worst in the order of Example 7, Example 11, Example 12, Example 10, and Example 13. Comprehensively comparing the advantages and disadvantages of hardness, yield strength, toughness, and hydrogen corrosion resistance and the actual difference, the quenching treatment parameters of the present application are better when the quenching temperature is 1120 to 1130°C and the cooling temperature is 75 to 90°C on the surface.

[0057] By comparing Example 7 with Examples 14 to 17, it can be seen that the difference lies in the different quenching process parameters. In the test results, the hardness and yield strength are from high to low in Example 7, Example 14, Example 15, Example 16, and Example 17, the toughness is from best to worst in Example 7, Example 15, Example 16, Example 14, and Example 17, and the hydrogen corrosion resistance is from best to worst in Example 7, Example 16, Example 17, Example 15, and Example 14. Comprehensive comparison and actual difference of hardness, yield strength, toughness, and hydrogen corrosion resistance, the tempering treatment parameters of the present application are 769 to 780°C at the tempering temperature, and the tempering temperature time is 1.6 min / mm (tube wall thickness).

[0058] By comparing Example 7 and Example 22, it can be seen that during the preparation process of Example 7, the hot pipe was placed in a nitrogen protective atmosphere for cooling, and during the preparation process of Example 22, the hot pipe was placed in an argon protective atmosphere for cooling; in the test results, the toughness of Example 7 is better than that of Example 22, and the hardness, yield strength and hydrogen corrosion resistance of Example 7 are better than those of Example 22. In fact, since the cooling is carried out under a nitrogen protective atmosphere after tempering, on the one hand, the carbon element precipitation structure and distribution on the surface of the stainless steel pipe are reduced due to oxidation, thereby avoiding the resulting reduction in the surface hardness and yield strength of the stainless steel pipe. On the other hand, the surface of the stainless steel pipe is nitrided during the cooling process, and the surface of the stainless steel pipe is micro-alloyed and modified to improve the hydrogen corrosion resistance of the stainless steel pipe surface.

[0059] In combination with Example 7 and Examples 18 to 21, the difference is that the nitrogen content in the cooling atmosphere of the heat pipe material is different. In the test results, the hardness and yield strength are from high to low in Example 7, Example 21, Example 20, Example 19, and Example 18, the toughness is from good to bad in Example 7, Example 18, Example 20, Example 19, and Example 21, and the hydrogen corrosion resistance is from good to bad in Example 7, Example 20, Example 21, Example 19, and Example 18. Comprehensively comparing the advantages and disadvantages of hardness, yield strength, toughness, and hydrogen corrosion resistance and the actual difference, the nitrogen content in the nitrogen protective atmosphere used for the heat pipe material of the present application during cooling is preferably 82.9-84.6 vol%.

[0060] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of protection required by the present invention, it will be protected by the patent law.

Claims

1. A high-toughness, hydrogen-corrosion-resistant stainless steel pipe, characterized in that: The following components are included in mass fraction: C 0.11~0.15%, Si 0.4~0.6%, Cr 18.2~19.6%, Ni 3.2~4.6%, V 0.7~0.9%, Mo 1.2~2.4%, Co 1.1~1.7%, Yi 0.8~1.1%, S≤0.01%, P≤0.002%, Others are Fe and unavoidable impurities; It is obtained by rolling, quenching and tempering the tube billet.

2. A high-toughness, hydrogen-corrosion-resistant stainless steel pipe, characterized in that: The following components are included in mass fraction: C 0.11~0.15%, Si 0.4~0.6%, Cr 18.2~19.6%, Ni 3.2~4.6%, V 0.7~0.9%, Mo 1.2~2.4%, Co 1.1~1.7%, Yi 0.8~1.1%, Ta 0.4-0.6%, wherein Ta is added as tantalum carbide; S≤0.02%, P≤0.002%, Others are Fe and unavoidable impurities; It is obtained by rolling, quenching and tempering the tube billet.

3. A method for preparing a high-toughness hydrogen corrosion-resistant stainless steel pipe according to claim 1 or 2, characterized in that: The following steps are involved: Smelting, continuous casting, drilling, rolling, quenching and tempering.

4. The method for preparing a high-toughness hydrogen-corrosion-resistant stainless steel pipe according to claim 3, characterized in that: The quenching temperature is 1120-1130°C, and the cooling temperature is 75-90°C on the surface.

5. The method for preparing a high-toughness hydrogen corrosion-resistant stainless steel pipe according to claim 4, characterized in that: The tempering temperature is 769-780° C., and the tempering temperature time is 1.6 min / mm (tube wall thickness).

6. The method for preparing a high-toughness hydrogen corrosion-resistant stainless steel pipe according to claim 3, characterized in that: The tempered stainless steel pipe is cooled to room temperature in a protective atmosphere containing nitrogen.

7. The method for preparing a high-toughness hydrogen corrosion-resistant stainless steel pipe according to claim 6, characterized in that: The nitrogen content in the nitrogen-containing protective atmosphere is 82.9-84.6 vol%.

8. The method for preparing a high-toughness hydrogen corrosion-resistant stainless steel pipe according to claim 2, characterized in that: The following steps are involved: Smelting, continuous casting, drilling, rolling, quenching and tempering. The tantalum carbide is added to molten steel during the smelting process. The tantalum carbide is added in the form of a composite solid solution of tantalum carbide and iron-nickel alloy.

Citation Information

Patent Citations

  • Method for producing a hot press cured component, use of a steel product for producing a hot press cured component, and hot press cured component

    CN102803519A

  • High-temperature-resistant seamless stainless steel tube and preparation method thereof

    CN106319396A

  • Duplex stainless steel and preparation method thereof

    CN107083524A

  • Ultrahigh-strength maraging stainless steel with multiphase strengthening and preparation method thereof

    US20230072654A1